A Multicenter, Phase 2, Randomized, Placebo-Controlled, Double-Blind, Parallel-Group, Dose-Finding Trial of the Oral Factor XIa Inhibitor Asundexian to Prevent Adverse Cardiovascular Outcomes After Acute Myocardial Infarction. Issue 16 (27th August 2022) - Rao, Sunil V.; Kirsch, Bodo; Bhatt, Deepak L.; Budaj, Andrzej; Coppolecchia, Rosa; Eikelboom, John; James, Stefan K.; Jones, W. Schuyler; Merkely, Bela; Keller, Lars; Hermanides, Renicus S.; Campo, Gianluca; et al.
Abstract : Background: Oral activated factor XI (FXIa) inhibitors may modulate coagulation to prevent thromboembolic events without substantially increasing bleeding. We explored the pharmacodynamics, safety, and efficacy of the oral FXIa inhibitor asundexian for secondary prevention after acute myocardial infarction (MI). Methods: We randomized 1601 patients with recent acute MI to oral asundexian 10, 20, or 50 mg or placebo once daily for 6 to 12 months in a double-blind, placebo-controlled, phase 2, dose-ranging trial. Patients were randomized within 5 days of their qualifying MI and received dual antiplatelet therapy with aspirin plus a P2Y12 inhibitor. The effect of asundexian on FXIa inhibition was assessed at 4 weeks. The prespecified main safety outcome was Bleeding Academic Research Consortium type 2, 3, or 5 bleeding comparing all pooled asundexian doses with placebo. The prespecified efficacy outcome was a composite of cardiovascular death, MI, stroke, or stent thrombosis comparing pooled asundexian 20 and 50 mg doses with placebo. Results: The median age was 68 years, 23% of participants were women, 51% had ST-segment–elevation MI, 80% were treated with aspirin plus ticagrelor or prasugrel, and 99% underwent percutaneous coronary intervention before randomization. Asundexian caused dose-related inhibition of FXIa activity, with 50 mg resulting in >90% inhibition. Over a median follow-up of 368 days, the main safety outcome occurred in 30 (7.6%), 32 (8.1%), 42 (10.5%), and 36 (9.0%) patients receiving asundexian 10 mg, 20 mg, or 50 mg, or placebo, respectively (pooled asundexian versus placebo: hazard ratio, 0.98 [90% CI, 0.71–1.35]). The efficacy outcome occurred in 27 (6.8%), 24 (6.0%), 22 (5.5%), and 22 (5.5%) patients assigned asundexian 10 mg, 20 mg, or 50 mg, or placebo, respectively (pooled asundexian 20 and 50 mg versus placebo: hazard ratio, 1.05 [90% CI, 0.69–1.61]). Conclusions: In patients with recent acute MI, 3 doses of asundexian, when added to aspirin plus a P2Y12 inhibitor, resulted in dose-dependent, near-complete inhibition of FXIa activity without a significant increase in bleeding and a low rate of ischemic events. These data support the investigation of asundexian at a dose of 50 mg daily in an adequately powered clinical trial of patients who experienced acute MI. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04304534; URL: https://www.clinicaltrialsregister.eu/ctr-search/search ; Unique identifier: 2019-003244-79.